Kekerasan Seksual Terhadap Anak Penyandang Disabilitas - Br. Tarigan, Tesa Lonika; Rosmalinda (PT. Meja Ilmiah Publikasi, 2025)
This paper discusses how regulations and laws can protect children with disabilities from harm, particularly from those who may cause them harm. The main focus is on Law Number 1 of 2023 concerning the Criminal Code (KUHP), specifically Article 473, which addresses criminal penalties for sexual violence against children and individuals with disabilities. This research uses a normative legal approach, analyzing secondary data sources, including primary, secondary, and tertiary legal materials, such as books, academic journals, and credible online sources. The methodology employed is literature study and qualitative analysis to provide a comprehensive understanding of legal protections for children and individuals with disabilities. Article 473 stipulates that perpetrators of sexual violence against children and individuals with disabilities will face imprisonment of at least three years and up to fifteen years, along with fines from Class IV to VII. Law enforcement must take firm action to enforce these legal protections, ensuring the physical and psychological safety of these vulnerable individuals from any threats.